Zoonotic Diseases and Food Safety - Kumar, Ashok; Malik, S. V.S.; Dubal, Z. B.; Mendiratta, S. K. (Indian Farming, 2015)
At IVRI, the Division of Veterinary Public Health has been making continuous attempts on collection, characterization and documentation of zoonotic and food borne pathogens to ascertain the associated threats and assess and exploit their potential use in developing highly efficient diagnostics and biologicals using frontier technologies. The database on distribution and determinants of these diseases would be developed for effective utilization by health planners, scientists and allied workers engaged in health programmes.